Reading religous ritual with Ricoeur between fragility and hope - Gschwandtner, Christina M., 1974- (Studies in the thought of Paul Ricoeur., 2021)
Reading Religious Ritual with Ricoeur extends Ricœur's philosophical treatment of religion beyond an analysis of mythic symbols and the biblical texts to religious ritual practices. It also applies his broader hermeneutic lens to liturgical actions and practices in regard to religious truth, language, imagination, and identity.